Identification Of Bioactive Components and Its Biological Activities of Ethanolic Extracts of Turmeric ana Aloevera - A Gc-Ms Study - حسن, غادة; نهلة ابراهيم ,; عقيل حجوز,; رنا عيسى , (Latakia University Journal -Biological Sciences Series, 2023)
The aim of This study identify the biological active Chemical constituents of the ethanolic extracts of Aloe vera gel and rhizome of Turmeric by Mass spectrometry (GC/MS). The results showed three new components in aloe vera gel extracts : 9,12- Octadecadienoic acid, methyl ester (Fatty acids) 2.34% Anthiaergosta -5,7,9,22-tetraene (hydrocarbons) 5.56%, Phthalic acid ,2-ethylhexyl tridecyl ester(esters) 12.26%, we found also some new components in turmeric rhizomes extracts: Acetic acid ,2,4-(xylyl), 4-Methyl-N- (4-methyl-furazan-3-yl) benzamide, Benzaldehyde,3-hydroxy-oxime, Beta- Myrcene, Tridecanoic acid, 9,17-Octadecadienal, 1,3,8-p- Menthatriene, 2,4- Methoxy vinylphenol, Benzofuran,2,3-dihydro, Benzene, 1-(1,5-dimethyl-4-hexenyl)-4-methyl, 6-Octen-1-yn-3-ol,3,7-dimethyl,in addition to Tumerone , Curlone.